2016
DOI: 10.1186/s13054-016-1560-6
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative statin therapy in cardiac surgery: a meta-analysis of randomized controlled trials

Abstract: BackgroundSeveral studies suggest beneficial effects of perioperative statin therapy on postoperative outcome after cardiac surgery. However, recent randomized controlled trials (RCTs) show potential detrimental effects. The objective of this systematic review is to examine the association between perioperative statin therapy and clinical outcomes in cardiac surgery patients.MethodsElectronic databases were searched up to 1 November 2016 for RCTs of preoperative statin therapy versus placebo or no treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 66 publications
2
33
0
3
Order By: Relevance
“…In 2016, ICD 9 classification, which was still used in our hospital, was revised to ICD-10; however, this did not affect our assessment. Perioperative statin therapy for metabolic syndrome has gained popularity in recent years [18,19]. Since patients with cardiovascular operations showed a higher risk for developing surgical complications, the counteraction of statins on the detrimental effect help in combating surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, ICD 9 classification, which was still used in our hospital, was revised to ICD-10; however, this did not affect our assessment. Perioperative statin therapy for metabolic syndrome has gained popularity in recent years [18,19]. Since patients with cardiovascular operations showed a higher risk for developing surgical complications, the counteraction of statins on the detrimental effect help in combating surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, contrary to expectation, recent trials in cardiac surgery found that perioperative statin administration was associated with an increased risk of AKI, particularly in statinnaïve patients [107][108][109]. A recent meta-analysis including these recent RCTs found a trend toward increase in mortality in patients receiving statins [110]. In vascular surgery, a recent meta-analysis highlighted lack of definitive evidence of beneficial effects of perioperative statin administration [111], as did a recent mRCT in noncardiac surgery [112].…”
Section: Statinsmentioning
confidence: 99%
“…17 However, randomized controlled trials have produced conflicting results on the ability of immediate preoperative statin therapy to reduce the risk of stroke after cardiac surgery. 18 The use of antiplatelet or anticoagulation medications is similarly controversial. Aspirin therapy administered within 48 hours of CABG surgery was shown to reduce the rate of stroke in a large, prospective study.…”
Section: Stroke Prevention In the Perioperative Settingmentioning
confidence: 99%